Pengaruh Vitamin D terhadap Sistem Imun Pasien Kusta - Rovanza, Florentina Ranni Eka (PT Kalbe Farma Tbk., 2025)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae. Vitamin D is a fat-soluble vitamin that plays an important role in bone metabolism with an anti-inflammatory and immune-modulating properties. Recent studies show a role of vitamin D on the immune system of leprosy patients. Vitamin D in its active form (1,25 (OH)2 D binds to the vitamin D receptor on macrophages. Vitamin D stimulates the production of cathelicidin and defesin, antimicrobial peptides that can kill Mycobacterium leprae. Vitamin D enhances the Th1 immune response by producing IL12, which is important against intracellular bacteria. Vitamin D suppresses excessive TH2 immune response to prevent disease progression. Vitamin D deficiency has a strong negative correlation with increased levels of pro inflammatory cytokines such as TNF -α. TNF-α, an inflammatory modulator, has been found to be significantly elevated in skin lesions of leprosy patients experiencing type 2 leprosy reactions. High levels of TNF-α play a direct role in myelin sheath damage, bone resorption stimulation, and inhibition of bone collagen synthesis. These factors likely explain clinical symptoms such as neurological disorders and disability in leprosy patients. Based on the above findings, vitamin D has effects on the immune system of leprosy patients.